2021
DOI: 10.3389/fimmu.2021.702971
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Antiviral Mechanisms of Two Viperin Homeologs in a Recurrent Polyploid Fish

Abstract: Polyploidy and subsequent diploidization provide genomic opportunities for evolutionary innovations and adaptation. The researches on duplicated gene evolutionary fates in recurrent polyploids have seriously lagged behind that in paleopolyploids with diploidized genomes. Moreover, the antiviral mechanisms of Viperin remain largely unclear in fish. Here, we elaborate the distinct antiviral mechanisms of two viperin homeologs (Cgviperin-A and Cgviperin-B) in auto-allo-hexaploid gibel carp (Carassius gibelio). Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 76 publications
2
11
0
Order By: Relevance
“…Each Cgptpn6 homeolog with three alleles was confirmed by FISH. Consistent with our previous studies (35,36), three green Cgptpn6-A signals and three red Cgptpn6-B signals were located on the three different chromosomes when simultaneously using Cgptpn6-A-BAC-DNA and Cgptpn6-B-BAC-DNA as probes respectively (Figure 1B). Syntenic alignment showed that gibel carp chromosome CgA16 and CgB16 both retained approximately 60% of the analyzed homologous genes in zebrafish chromosome 16 and had a conserved gene block (styk1-phc1-atn1-mlf2-ptpn6).…”
Section: Two Divergent Cgptpn6 Homeologs With Conserved Genomic Structure In Gibel Carpsupporting
confidence: 91%
See 4 more Smart Citations
“…Each Cgptpn6 homeolog with three alleles was confirmed by FISH. Consistent with our previous studies (35,36), three green Cgptpn6-A signals and three red Cgptpn6-B signals were located on the three different chromosomes when simultaneously using Cgptpn6-A-BAC-DNA and Cgptpn6-B-BAC-DNA as probes respectively (Figure 1B). Syntenic alignment showed that gibel carp chromosome CgA16 and CgB16 both retained approximately 60% of the analyzed homologous genes in zebrafish chromosome 16 and had a conserved gene block (styk1-phc1-atn1-mlf2-ptpn6).…”
Section: Two Divergent Cgptpn6 Homeologs With Conserved Genomic Structure In Gibel Carpsupporting
confidence: 91%
“…Numerous examples have proven that homeolog biased expression seems to be a rule rather than an exception (30). In our previous studies, homeolog bias occurred differently in different tissues (35,36,50); for example, Cgviperin-A was expressed higher than Cgviperin-B in the spleen and liver, whereas in the gill, the transcripts of Cgviperin-B were more abundant than Cgviperin-A (36). However, Cgptpn6-A was dominant in the 12 adult tissues (Figure 2), and poly I:C, poly dA:dT, and SVCV all induced higher upregulated expression of Cgptpn6-A relative to Cgptpn6-B (Figure 3).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations